2014
DOI: 10.2807/1560-7917.es2014.19.7.20709
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of silent introduction and sustained transmission of wild poliovirus type 1, Israel, 2013

Abstract: Poliovirus vaccine coverage in Israel is over 90%. The last nine birth cohorts have been vaccinated exclusively with inactivated polio vaccine (IPV). However, between February and July 2013 type 1 wild poliovirus (WPV1) was detected persistently in 10 and intermittently in 8 of 47 environmental surveillance sites in southern and central Israel and in 30 stool samples collected during July from healthy individuals in southern Israel. We report results of sequence and phylogenetic analyses of genes encoding caps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
60
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 24 publications
0
60
0
Order By: Relevance
“…Sequence analysis identified the virus isolates as WPV1 belonging to the SOAS lineage, with closest match to the virus isolated from sewage in Egypt in December 2012 [18]. The viral load in the sewage sample was calculated from the number of plaques isolated: by taking into consideration of the size of the sampled population, the number of faecal excretors of the virus could be roughly estimated to be tens or even hundreds of excretors, indicating ongoing indigenous circulation.…”
Section: Detection Of Soas-wpv1 Importation To Southern Israel and Inmentioning
confidence: 99%
“…Sequence analysis identified the virus isolates as WPV1 belonging to the SOAS lineage, with closest match to the virus isolated from sewage in Egypt in December 2012 [18]. The viral load in the sewage sample was calculated from the number of plaques isolated: by taking into consideration of the size of the sampled population, the number of faecal excretors of the virus could be roughly estimated to be tens or even hundreds of excretors, indicating ongoing indigenous circulation.…”
Section: Detection Of Soas-wpv1 Importation To Southern Israel and Inmentioning
confidence: 99%
“…1 The editorial was responding to California's firstin-the-nation broad medical-marijuana law and DEA agents' subsequent threats to revoke the DEA registrations of California physicians who suggested that a patient might benefit from marijuana as permitted by the new law. 2 California has now been joined by more than 20 additional states in permitting patients to possess marijuana on the advice of their physician (see table). There has, however, been no change in federal law -which still prohibits possession and sale of marijuana -and little change in the DEA's tactics.…”
Section: Lessons From a Publicmentioning
confidence: 99%
“…Since the last poliomyelitis outbreak in Israel in 1988, 1 the country has developed the capacity in our environmental laboratories to detect pathogens such as polioviruses in very low quantities within large volumes of sewage, and we have fully deployed this high-sensitivity detection on a national scale. This system routinely covered approximately 30 to 40% of the population in a representative fashion, 2 and it was substantially intensified beginning in June 2013, shortly after the detection of the wild poliovirus importation. The number of sewage sites being sampled increased from a range of 8 to 10 per month to 80 per month at the height of the effort, to keep up with poliovirus activity.…”
mentioning
confidence: 99%
See 2 more Smart Citations